2016
DOI: 10.1074/jbc.m115.694372
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Critical Prolines in Gloeobacter violaceus Ligand-gated Ion Channel (GLIC) Supports Conserved Gating Motions among Cys-loop Receptors

Abstract: Gloeobacter violaceus ligand-gated ion channel (GLIC) has served as a valuable structural and functional model for the eukaryotic Cys-loop receptor superfamily. In Cys-loop and other receptors, we have previously demonstrated the crucial roles played by several conserved prolines. Here we explore the role of prolines in the gating transitions of GLIC. As conventional substitutions at some positions resulted in nonfunctional proteins, we used in vivo non-canonical amino acid mutagenesis to determine the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…An important caveat is that this protein (accession code # AZS27833.1) differs from an earlier published sequence (accession code # ABW07339.1) by a single amino acid in the cys-loop (serine versus proline in ABW07339.1). This proline residue has been reported to be of critical importance for ligand-activation in the pLGIC family (Lummis et al, 2005;Rienzo et al, 2016), and highlights the role that a single residue can play in receptor activation.…”
Section: Discussion Expression and Agonist Activity Of Acetylcholine mentioning
confidence: 79%
“…An important caveat is that this protein (accession code # AZS27833.1) differs from an earlier published sequence (accession code # ABW07339.1) by a single amino acid in the cys-loop (serine versus proline in ABW07339.1). This proline residue has been reported to be of critical importance for ligand-activation in the pLGIC family (Lummis et al, 2005;Rienzo et al, 2016), and highlights the role that a single residue can play in receptor activation.…”
Section: Discussion Expression and Agonist Activity Of Acetylcholine mentioning
confidence: 79%
“…Notably, the three M1-205 variants (Trp, Gly, and Pro) with expanded forms of the open-state intrasubunit cavity also exhibited decreased H + sensitivity, in accordance with a critical role for the extracellular-facing portion of M1 in gating and modulation ( 37 ). Previous studies in GLIC ( 38 , 39 ), nACh ( 40 , 41 ), and 5-HT 3 receptors ( 42 , 43 ) have shown that disruption of backbone N hydrogen bonding at Pro-204—the most conserved transmembrane residue among all pLGICs ( 44 )—is not only permissive, but necessary for channel gating. It is plausible that bulky or helix-disrupting residues at adjacent position 205 could account for an increased barrier to relieving the M1 kink, decreasing agonist sensitivity but increasing accessibility of M2 from the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The conservation of the gating mechanism between bacterial and eukaryotic pLGICs is well documented by the available structures with the common allosteric regulatory sites for ligands and mutations (Sauguet et al, 2015; Bertozzi et al, 2016; Rienzo et al, 2016), together with the allosteric compatibility between eukaryotic and prokaryotic ECD/TMD domains to form functional chimeras (Duret et al, 2011; Moraga-Cid et al, 2015; Laverty et al, 2017). It is therefore tempting to speculate that the pre-activation transition of GLIC that we characterize here might have counterparts in human neurotransmitter-gated receptors.…”
Section: Discussionmentioning
confidence: 99%